SEASONAL INCIDENCE AND IMPACT OF SOME ABIOTIC FACTORS ON THRIPS, Scirtothrips dorsalis HOOD (THYSANOPTERA: THRIPIDAE) INFESTING MANGO CV AMRAPALI - PATEL, TWINKAL; SHUKLA, ABHISHEK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The seasonal incidence of mango thrips revealed that it first appeared from the third week of January. Thereafter, the thrips population increased continuously till the last week of March and reached to peak at 13th standard week. The maximum population was recorded during 11th to 14th standard week, after which the population started decreasing. The relationship of thrips population with weather parameters revealed that the incidence of thrips showed significant positive correlation with sunshine hours (r= 0.436). While, average relative humidity showed negative and significant correlation (r = -0.388) with mango thrips.